The Effect of Using Audio Visual Learning Media for News Text Material in Class VIII MTs Al-Hanafiyah Mojowarno Jombang - Hakim, Vira Aulia; Arisni Kholifatu Amalia Shofiani (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2024)
An activity that has been designed as well as possible, using learning media, where the media is expected to help students and teachers in teaching and learning activities. Learning media is a tool used to convey material to students. One of the learning media that is often used is audio-visual learning media, where this media is very easy to use and almost all schools have audio-visual media materials and tools. So this makes audio visual learning media very important and much needed in the world of education because it can help teachers make it easier to convey material, one of which is news text material. This research uses qualitative methods and obtains data through filling out questionnaires, interviews and classroom observations. This research was located at the MTs Al-Hanafiyah Mojowarno Jombang school. The research subjects were 11 students in class VIII MTs Al-Hanafiyah. The research results show that audio-visual learning media is very influential in delivering news text material. So it can build students' enthusiasm for studying news text material, as well as making it easier for students to understand news text material.